LIVING VALUES EDUCATION PROGRAM DALAM PEMBELAJARAN DARING SEKOLAH DASAR - An-Nisa Apriani; Wilda Isti Chomariyah; Ahmad Sukaris (Taman Cendekia: Jurnal Pendidikan Ke-SD-an, 2021)
This study aimed to describe the process of instilling character in online learning through the Living Values Education Program (LVEP). The type of research used in this research was literature study. The data in this study were secondary data from books, journals, and other relevant sources. Data analysis in this literature review was content analysis. The results showed that the LVEP which included the values of life such as the value of cooperation, freedom, happiness, honesty, humility, love, peace, respect, responsibility, simplicity, tolerance, and unity was one of the effective programs in instilling character in online learning. Living ValuesEducation Program (LVEP) in online learning included activities of reflection, imagination, dialogue, communication, creation, writing, expressing oneself through art, and playing with the values taught. LVEP in online learning was able to help and encourage students to access their creativity and talents to explore and develop universal values. LVEP made children more self-confident, more appreciative of others and demonstrated positive social and personal skills improvement, even LVEP had a positive influence on the character development of students.